Postpartum Depression in a General Pediatric Practice: Practical Methods for Improving Screening and Referrals. (August 2016) - Friedman, Suzanne; Rochelson, Ellis; Fallar, Robert; Mogilner, Leora
Postpartum depression (PPD) is a common problem in new mothers. Untreated PPD is associated with behavioral and developmental problems in children. We examined the effects of an educational session about PPD and modification of the electronic medical record (EMR) on providers' screening for PPD. An education session was given to the physicians and pre and post surveys compared comfort and self-reported screening. Following the EMR change, a retrospective chart review was conducted from three time periods: group 1—before the conference, group 2—after the conference but before EMR change, and group 3—after screening in the EMR. Documented screening increased from 0% in group 1, to 2% in group 2, to 74% in group 3 ( P < .001). Ten percent screened positive, but only 14% had documented referrals to a provider for treatment. The combination of provider education and screening questions integrated into the EMR enhanced PPD screening rates among physicians in a busy practice.